Fenomenologia das representações - sobre a equivocação do termo representação na tese todos os atos ou são representações ou se fundam em representações arrazoada por Edmund Husserl na V Investigação das Investigações lógicas - Madureira, Jonas Moreira (2008)
In this study, it is justified the phenomenology of the representations, found in the V Investigation of the Investigations logics of Edmund Husserl. More specifically, it refers to about the husserlian analysis of the equivocation of the term representation in the thesis all the acts either are representations or are established in representations . To explain the equivocation of the term representation especially in what concerns to the cited thesis and not in what it relates to the general use of the term -, it is necessary to discriminate the equivocation s elements. In the V Investigation, Husserl analyzes only four of them, which are: the mere representation (bloβe Vorstellung); the matter of act (Aktmaterie); the nominal act (nominaler Akt); the objective act (objektivierender Akt). From this quadruple equivocation, Husserl presents three possible interpretations of the thesis: (1) all act either is one mere representation or have one matter of act as a fundamental component in the intentional essence; (2) all act either is one nominal act or it is established in one or several nominal acts; (3) all act either is one objective act or it is established in one objective act. Thus, the main objective of this dissertation is to explain exactly these three interpretations. For this, it becomes necessary to clarify the husserlian structure of act, once the understanding of such structure is conditio sine qua non for the understanding of Husserl s the three interpretations